2022
DOI: 10.3390/ijms23179888
|View full text |Cite
|
Sign up to set email alerts
|

Copper Modulates Adult Neurogenesis in Brain Subventricular Zone

Abstract: The subventricular zone (SVZ) in lateral ventricles is the largest neurogenic region in adult brain containing high amounts of copper (Cu). This study aims to define the role of Cu in adult neurogenesis by chelating labile Cu ions using a well-established Cu chelator D-Penicillamine (D-Pen). A neurosphere model derived from adult mouse SVZ tissues was established and characterized for its functionality with regards to neural stem/progenitor cells (NSPCs). Applying D-Pen in cultured neurospheres significantly r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 69 publications
(92 reference statements)
0
10
0
Order By: Relevance
“…Understanding neural stem cell regulation is essential to improve our stem cell therapy for stroke for stroke [26]. Nestin and DCX are well known markers of cell proliferation in the SVZ [27]. In a recent study, it was shown that nestin is expandable in vitro and its expression persists in neurospheres grown in vitro after 7 days in culture derived from the subventricular zone of adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding neural stem cell regulation is essential to improve our stem cell therapy for stroke for stroke [26]. Nestin and DCX are well known markers of cell proliferation in the SVZ [27]. In a recent study, it was shown that nestin is expandable in vitro and its expression persists in neurospheres grown in vitro after 7 days in culture derived from the subventricular zone of adult mice.…”
Section: Discussionmentioning
confidence: 99%
“…Primary neurospheres, which were formed 6 days after the initial seeding, were collected for Trypsin dissociation and the cell suspension was then reseeded into a 96-well U-shaped-bottom microplate (0.1 mL/well, 1.0 × 10 4 cells/mL in NBM enriched with growth factors and heparin) for secondary neurosphere formation. After 24 hrs, the secondary neurospheres were formed with nearly identical diameters (Liu et al 2022b). These secondary neurospheres were collected and resuspended in NBM for subsequent plating onto the PLO-coated glass bottom in the lower chamber.…”
Section: Co-culture Of Svz Neurospheres With Cp Tissuesmentioning
confidence: 99%
“…qPCR was performed as previously described (Liu et al 2022b). Briefly, total RNA was extracted from samples using TRIzol reagent and Direct-zol RNA Microprep kit.…”
Section: Quantitative Polymerase Chain Reaction (Qpcr)mentioning
confidence: 99%
See 2 more Smart Citations